Pharmacokinetics of the anti-human immunodeficiency virus nucleoside analog stavudine in cynomolgus monkeys. - Kaul, S (1993)
Stavudine was administered (15 mg/kg of body weight) intravenously and orally to two monkeys in a randomized crossover study. Plasma and urine samples were analyzed for stavudine by high-performance liquid chromatography, and pharmacokinetic parameters were derived by a noncompartmental method. Total body clearance of stavudine was 0.64 liters/h/kg, with a steady-state volume of distribution of 0.68 liters/kg, a terminal half-life of 0.83 h, a urinary recovery of 44%, and an oral bioavailability of 80%. These values were reasonably similar to those reported for patients with AIDS or AIDS-related complex.